Evaluation of Faculty of Readiness in Achieving the Entrepreneurial University Study Agenda in the Faculty of Economics and Business, Institute of Business Dili Timor Leste - Domingas de Fatima Xavier; Astri Ghina (GoAcademica Research & Publishing, 2022)
Entrepreneurial University is a phenomenon that is considered important today by universities to increase university competitiveness in increasing excellence in aspects of teaching, research, and community service. If the university does not become an entrepreneurial university, it will hinder national development and international competitiveness. teaching universities need to create entrepreneurial universities and that is very important to achieve sustainable economic growth in a country and also being an Entrepreneurial University (EU) does not belong to any country, thus any University has the right to become an EU wherever the university is located. This study uses a mixed method and sequential explanatory desing which conducts quantitative research first by obtaining data from questionnaires distributed to respondents in the economics and business faculties and followed by qualitative methods by conducting interviews with resource persons. The purpose of this study is to evaluate the readiness of the faculty in realizing the entrepreneurial university agenda. The measuring instrument used by the OECD 2019 researchers is the measure and there are eight aspects that must be evaluated and the results of the evaluation there are 3 aspects that need focus and improvement by the faculty because they are considered to have low respondent scores in realizing the EU agenda, namely Entrepreneurship Teaching and Learning, Digital Transformation and Capability and Measuring Impact.